The Importance of Using Personal Protective Equipment (PPE) at ASD Transko Gelatik - Tuan Son Le (PT. Alpha Trianguli Australis, 2025)
Indonesia is a maritime archipelago with abundant natural resources from marine products and other natural resources. Ships are the only means of transportation that connects many things from various regions through sea routes. This study aims to understand the importance of using personal protective equipment (PPE) on the ASD Transko Gelatik ship. Qualitative research methodology is suitable for research that focuses on understanding the processes, meanings, or motivations that underlie certain behaviors or phenomena, especially those that cannot be explained by numbers or statistics. The results of this study are: 1) The use of PPE on the ASD Transko Gelatik ship including the types of PPE used on the ASD Transko Gelatik ship, the procedures for using PPE on the ship, and the role of PPE in ship operations; and 2) Barriers and solutions to the use of PPE on the ASD Transko Gelatik ship including lack of awareness and knowledge about PPE, inadequate availability and quality of PPE, discomfort in using PPE, a work culture that does not support the use of PPE, lack of proper maintenance and storage of PPE, and language and communication barriers.